Reconstruction of Business Legal Ethics from the Perspective of the Principles of Good Faith and Contractual Fairness - Narwadi, N Agus Adyatma; Budiana, I Nyoman; Kurniawan, I Gede Agus (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Contracts in modern business practice serve not only as binding legal instruments but also as vehicles for realizing ethical values between parties. However, in reality, many commercial agreements are drafted solely based on the principle of freedom of contract, without adequate regard for the principles of good faith and contractual justice, which are essential to ensuring a fair balance of rights and obligations. The legal issue addressed in this study concerns the absence of explicit regulation regarding ethical standards in contract performance, particularly the role of good faith as a moral and legal foundation binding the parties. This study aims to reconstruct business legal ethics by positioning the principles of good faith and contractual justice as normative elements within Indonesia's civil law system. The research adopts a normative juridical method, utilizing both conceptual and statutory approaches, supported by doctrinal analysis and relevant jurisprudence. The findings indicate that the principle of good faith, as stipulated in Article 1338(3) of the Indonesian Civil Code, holds strong potential as a legal basis for assessing the moral legitimacy of contract execution. Similarly, the principle of contractual justice may serve as a corrective mechanism against imbalanced or exploitative business practices. Therefore, reconstructing business legal ethics through these two principles is crucial for developing a contractual system that is fair, morally grounded, and responsive to evolving socio-economic dynamics.